Performance comparison and analysis of Linux block I/O schedulers on SSD - Abdullah Yildirim; Yunus Ozen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
A computer system’s one of the slowest operation is disk seek operation. Sending out read and write requests to the block devices such as disks as soon as the request arrives results in poor performance. After performing sorting and merging operations, the operating system kernel issues block I/O requests to a disk for improving the overall system performance. The kernel subsystem to perform scheduling the block I/O requests is named as the I/O scheduler. This paper introduces performance comparison and detailed analyses of Deadline, CFQ, Noop and BFQ block I/O schedulers that are contained in the Linux 4.1x kernel. The tests have been carried out on an SSD block device that is common in hardware combinations of both personal and professional use-case scenarios. The performance of the schedulers has been evaluated in terms of throughput. Each scheduler has advantages in different use-case scenarios and provides better throughput in a suitable environment.